Overview of American Heart Association / American College of Cardiology guidelines 2017 for management of patients with valvular heart disease - M.Т. Vatutin; G.A. Smyrnova; G.G. Taradin; Yu.P. Gritsenko; K.S. Gasendich (Кардіохірургія та інтервенційна кардіологія)
n June 2017, Circulation journal published updated recommendations of the American Heart Association and the American College of Cardiology (AHA / ACC) on the management of patients with valvular heart disease. The main provisions of this manual are set out in this message. It should be emphasized that the recommendations written by leading US experts in this field are set out clearly, using a variety of tables and figures, which will undoubtedly make them a desktop guide to action for most practitioners in the following years. As usual, when creating such guidelines, the authors were guided by evidence-based methodology using the classes of recommendations and levels of evidence.